A CASE OF MULTISYSTEM ANOMALIES ASSOCIATED WITH GASTROSCHISIS IN THE UNBORN FETUS – CASE REPORT WITH POST-DELIVERY CORRELATION - DR. KUKU MARIAM SURESH; DR. V. CHANDRASEKAR; DR. K. KANAKARAJ (International Journal of Pharma and Bio Sciences, 2014)
Gastroschisis is a congenital anomaly which shows extra abdominal herniation of fetal bowel loops, occasionally with portions of liver/ stomach, into the amniotic cavity through a paraumbilical defect in the anterior abdominal wall. The defect is usually right sided. Gastroschisis is decreasing in incidence owing to early detection by the advanced techniques in imaging and more efficient and thorough antenatal assessment. Omphalocoele is mostly associated with other chromosomal anomalies. On the contrary, gastroschisis is not alwaysaccompanied by a fixed set of anomalies except in 7 – 30% cases wherein anencephaly, cleft lip and palate, ectopia cordis, ASD, diaphragmatic hernia scoliosis, syndactyly, amniotic band and intestinal atresias. However this 25 year old primi gravida at 28 weeks, showed elevated maternal sAFP, short femur, cardiomegaly with severe pulmonary hypoplasia, median cleft lip, bilateral echogenic kidneys with renal cysts, diaphragmatic hernia, umbilical cord cyst and polydactyly with bilateral equinus deformity may occur. The unusual permutation of anomalies seen in this case is what makes it a rare entity worth discussion.Ultrasound was indicated by a clinical IUGR and done for anomaly screening. One week later, she returned following intrauterine fetal demise after which imaging modalities were employed to confirm the antenatal findings. This study emphasizes the need for strict antenatal screening and suspicious eye to rule out even unrelated anomalies in each case